Multi-Wavelength Brillouin-Erbium Photonic Crystal Fiber Lasers - Mohd Nasir, Mohd Narizee (2010)
A multi-wavelength Brillouin-erbium fiber laser (BEFL) in a Fabry-Perot linear cavity is demontrated. The fiber laser utilizes a Brillouin pump pre-amplification techniques intended for efficient Brillouin pump source.